A chronicle of PA journals. Issue 2 (February 2017) - Hooker, Roderick S.
Abstract : ABSTRACT: At its semicentennial mark, the PA profession appears to be flourishing. Over the past 50 years, a number of journals have emerged to highlight the development of the profession and offer observations on it. The Physician Associate Journal, launched in 1970, was the first foray into PA reporting. Following this small effort, a dozen journals or newspapers came into print, lasted for a while, and then were replaced or died. Of journals that survived to the present, four are in English and one in Dutch. Three of the five journals are association-based, and four produce clinical articles; publication is monthly, quarterly, or semiannually. Two journals produce original health services research or studies on the PA education process and have citable track records. Readership of all journals is growing, and collectively these periodicals produce a body of scholarly work that clarifies the PA as a healthcare professional growing on a world stage. This article describes the journalistic history of one aspect of PA development.